Penerapan Model Pembelajaran Kooperatif Tipe Numbered Heads Together Menggunakan Media Manipulatif Papan Refusi untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis Siswa SMP - Setiawan (Multiverse: Open Multidisciplinary Journal, 2022)
The low ability of students to understand mathematical concepts is due to the low ability of students to understand mathematical concepts and the lack of activeness of students in participating in the learning process. This study aims to describe the increase in the ability to understand students' mathematical concepts by applying the NHT type cooperative learning model using the Refusion Board manipulative media on relations and functions material. This type of research is a type of classroom action research. The subjects of this study were 20 students in class VIII-2 of SMP Negeri 4 Bukit. As for the results obtained from the two actions in this study, namely (1) Learning outcomes for the ability to understand students' mathematical concepts increased or completed with a percentage of 55% in action I increased to 85% in action II. (2) The activity of students participating in learning has increased, namely 70% in action I to 82.22% in action II. (3) The teacher's ability to manage learning is in the "good" category. There was an increase in the percentage in the implementation of action I by 73.57% to 84.28% in action II. Based on the results of the comparison of the percentages of the two stages, it can be concluded that the application of the cooperative learning model of the numbered heads together type using the refusion board manipulative media can improve students' understanding of mathematical concepts.